From context to text in contractual interpretation: Is there really a problem with the plain meaning rule? - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2016)
Much of the contemporary scholarship on contractual interpretation is staunchly against a textual analysis, by which a court can only depart from the plain meaning of a contract exceptionally. It is therefore no surprise that scholars have reacted negatively to the spate of recent cases where the English courts have re-emphasized the plain meaning of the text in contractual interpretation. Yet one cannot help but wonder whether a textual analysis is really so problematic when courts across the common law world have re-embraced it. Drawing from both theoretical and comparative perspectives, this paper suggests that a focus on the text in contractual interpretation, and the corresponding application of the plain meaning rule, is to be welcomed and not scorned.